Dyscard - Dyslexia-Friendly Card Game / Dayang Balqis Romzi … [ et al.] - Romzi, Dayang Balqis; Zainalariffin, Intan Syazana; Mohd Khairul Affzan, Nur Damia Iwana; Sheik Alavuddeen, Sheik Amirul Haziq; Anuar Rusydi, Syeikh Alauddin Rafdi; Abdul Azis, Rafidah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Our team has developed an engaging educational toy called Dyscard, a Dyslexia-Friendly Card Game, to help ease the difficulties dyslexic youngsters encounter when learning to read. Dyscard is, like its name suggests, a card game that is specifically made to help children with learning disabilities called ‘dyslexia’. This game involves interactive features specifically designed to support dyslexic children in their reading journey.